PENGARUH UPAH TERHADAP KEPUASAN KERJA - Bedjo Santoso Sakad (Jurnal Ekonomi dan Bisnis, 2016)
Gold dinar activists proposed gold dinar as money physically to be implemented in the current monetary system. Some efforts have been done for 3 decades but the result is not significant. Some proponent then come up to propose gold is just as measurement of value combined to infrastructures of ICT, however, the design is not specify yet. Therefore, this paper attempt to explore a framework mobile payment system based on gold as measurement of value a case study in Aceh. Design method is used to develop the model. Data is taken from observation, library, and secondary sources. The research is qualitative employed deductive analysis. Mobile payment system commodity money based on gold as measurement of value is the best way to implement gold as money in the current monetary system initiated by any communities or societies. The proposed model is enabling customers; whether individual or business for conducting any transactions efficiently and easily by using mobile phone.Â  Besides that, the proposed model has several advantages in term of economic, social and Islamic value.